Barriers and facilitators to the implementation of a practice programme for upright positions in the second stage of labour in China: A qualitative study. (November 2022) - Zang, Yu; Lu, Hong; Zhao, Ling; Zhang, Huixin; Hu, Yinchu; Fu, Li
Abstract: Objective: Upright positions in the second stage of labour are recommended by many labour and birth guidelines, but they have not been widely used in China and the implementation varies greatly. Given this, we developed a Practice Programme for Upright Positions in the Second Stage of Labour (UPSSL Programme). Whether the UPSSL Programme can be translated into action in the local context is a crucial issue that needs to be further explored. This study aimed to explore barriers and facilitators to the implementation of the UPSSL Programme in the Chinese context to facilitate the integration of evidence and routine clinical practice. Design: A descriptive qualitative design was adopted. Setting: The study was conducted in the maternity unit of a tertiary general hospital in China. Participants: A purposeful sampling was used to recruit midwives, obstetricians and their leaders. Data were collected through semi-structured face-to-face interviews. The Consolidated Framework for Implementation Research was used to guide the development of interview guide and the analysis of qualitative data. The study was reported following the Standards for Reporting Qualitative Research. Findings: Twelve eligible participants were interviewed, including eight midwives, two obstetricians, the head nurse of the delivery room, and the head of the maternity unit. Eight barriers and 10 facilitators were identified by using the directed content analysis. The barriers to implementing the UPSSL Programme were professionals' concerns about the potential risks of the programme ( relative advantage ), higher complexity ( complexity ), placement method of upright positions presented without pictures ( design quality & packaging ), staff shortage ( cost ), limited understanding of parturients' needs ( patient needs & resources ), lack of a training protocol for professionals ( available resources ), professionals' limited knowledge and skills in the programme ( knowledge & beliefs about the intervention ), and lack of confidence in the successful implementation of the programme ( self-efficacy ). Key conclusions: Participants expressed several barriers and facilitators to implementing the UPSSL Programme in clinical practice in the Chinese context. Implications for practice: The findings provide a reference for the development of targeted implementation strategies that could promote the integration of evidence and routine clinical practice, and thus facilitate the normative application and promotion of upright positions in China.